Understanding care homes safety: culture and safety in non-mainstream care settings - Gartshore, Emily (2021)
Background The care home sector provides 24-hour residential care or nursing care to more than 450,000 vulnerable older people in the UK with complex needs and high levels of dependency. These services face many challenges in relation to funding, increasing demand, staff shortages and relying on an unregistered workforce with almost 40% possessing no qualifications. Care homes present a unique setting that provides care to individuals at significant risk of harm but has received little attention or research. Care homes provide a particularly rich context in which to study safety, as they are inherently complex organisations that have historically suffered many catastrophic failures and scandals and continue to struggle to achieve safety goals.